Firmware Design for a Mechatronic Chordophone - Tait, Alex (Wellington Faculty of Engineering Symposium, 2023)
Azure Talos is a mechatronic chordophone that is theoretically capable of producing many of the expressive sounds and techniques of a human guitar player. However, despite its potential, Azure Talos was inherited in an incomplete state. To achieve full functionality, an entire firmware architecture was designed and implemented. Hardware issues were then identified and remedied. A User Interface was then implemented to facilitate operation by non-mechatronic composers. The result is a fully functioning mechatronic chordophone that is capable of levels of expressivity beyond any comparable devices found in the literature.